Prevalence of Psychiatric Comorbidities and Behavioral Risk Factors in Cardiovascular Disease Patients - Shah, Sanjeev; Sah, Chanda; Dhungana, Manoj; Khan, Mahmud Alam (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION: Decades of research has revealed several links between cardiovascular diseases (CVDs) and mental illness, and has even suggested that both may actually cause one another. Emerging research is beginning to uncover high prevalence of behavioral risk factors in patients with mental illness that may lead to cardiovascular disease. MATERIAL AND METHODS: A descriptive cross-sectional study was designed to assess the prevalence of psychiatric comorbidities in cardiovascular disease patients and to identify the behavioral risk factors in them. A semi-structured questionnaire including Self- Reporting Questionnaire (SRQ-20) by WHO was used to screen psychiatric symptoms among 190 purposively selected samples. Data were analyzed by using descriptive and inferential statistics with SPSS version 20.0 RESULTS: Among the 190 respondents, 150 (78.95%) were SRQ positive and table 1 shows majority (63.33%) was male. Highest proportion (60%) of the respondents was included in the age group of 40-64 years. Majority of cardiac morbidity was ischemic heart disease (55.79%). Respondents diagnosed with some kind of cardiac disease were suffering from depression (53.33%), anxiety disorder(38%) and panic disorder (8.67%). Behavioral risk factors present in respondents were smoking (90%) and alcohol abuse (90%) and more than half (65.33%) and (56%) had obesity and physical inactivity as behavioral risk factors respectively. CONCLUSION: Health care professionals will need to expand their use of standardized screening tools that capture psychosocial factors in the CVDs population. Thus it can help in prevention and treatment of such comorbidities.